STRATEGI EVALUASI DAN UPGRADE SISTEM INFORMASI DALAM MENGHADAPI TRANSFORMASI DIGITAL ORGANISASI - Maila Rosidah; Saipul Annur; Ade Rosad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze strategies for evaluating and upgrading information systems in elementary schools to support digital transformation in education. The research employed a qualitative approach using library research methods by reviewing relevant books, scientific journals, and policy documents published within the last decade. The data were analyzed through content analysis techniques involving data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that effective digital transformation in elementary schools requires an integrated strategy consisting of system monitoring, information system auditing, preventive and corrective maintenance, and systematic system upgrades. System monitoring ensures performance stability and service quality, while information system audits strengthen governance, security, and accountability. Preventive and corrective maintenance maintains operational continuity, and system upgrades enable schools to adapt to technological advancements and evolving educational needs. The study concludes that sustainable evaluation and upgrade strategies are essential to ensure that information systems function not only as administrative tools but also as strategic instruments to enhance the quality of educational services in the digital era.